2016
DOI: 10.1002/anie.201508227
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amaryllidaceae Constituents and Unnatural Derivatives

Abstract: This update covers the syntheses of Amaryllidaceae alkaloids since the publication of the last major review in 2008. A short summary of past syntheses and their step count is provided for the major constituents; pancratistatin, 7-deoxypancratistatin, narciclasine, lycoricidine, lycorine, and for other natural constituents, as well as for unnatural derivatives. Discussion of biological activities is provided for unnatural derivatives. Future prospects and further developments in this area are covered at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 242 publications
(671 reference statements)
0
71
0
1
Order By: Relevance
“…For instance, several studies have demonstrated that lycorine displays remarkable efficacy in the suppression of tumorigenesis (14,(19)(20)(21)(22)(23). However, the underlying mechanism involved remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, several studies have demonstrated that lycorine displays remarkable efficacy in the suppression of tumorigenesis (14,(19)(20)(21)(22)(23). However, the underlying mechanism involved remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although the targets or mechanisms of lycorine are still undefined, the dominant biological effects and low cytotoxicity of lycorine render it as a potential clinical drug or lead. For instance, it has received much attention as a promising anticancer agent for bladder cancer, cervical cancer, leukemia, prostate cancer, and multiple myeloma (14,(19)(20)(21)(22)(23). However, the defined molecular mechanisms underlying lycorine-regulated suppression of tumorigenesis remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The commercial ( S )‐2‐(methoxymethyl)pyrrolidine [( S )‐ 273 e ] was proven to be the most effective substrate leading up to 81 % ee of (−)‐ 270 (>99 % ee after crystallization). This accomplishment was also employed in Alonso's creative synthesis of (+)‐pancratistatin (the furyl unit in 270 was replaced by the aromatic A‐ring common to the Amaryllidaceae alkaloids) . The best conditions to obtain (+)‐ 270 required for the enantioselective synthesis of Sato's intermediate 158 involved the utilization of ( R )‐2‐(methoxymethyl)pyrrolidine [( R )‐ 273 e ] and provided 270 in 39 % yield with 77 % ee or in 42 % with 74 % ee, depending on the solvent.…”
Section: Synthesis Of Ttxmentioning
confidence: 99%
“…Natural products possess multiple bioactivities and serve as excellent drug leads for cancer treatment [5][6][7]. Lycorine, an active alkaloid extracted from a common herbal medicine (Lycoris radiate), was reported to possess anti-viral, anti-inflammatory and anti-cancer activities [8][9][10]. Notably, it has been found that lycorine can suppress the development of various malignant tumors, including multiple myeloma, hepatocellular carcinoma, and prostate cancer [11][12][13].…”
mentioning
confidence: 99%